Jaringan Pesantren di Jawa Barat Tahun 1800-1945: Critical Review atas Disertasi â€œJaringan Pesantren di Priangan 1800-1945â€ Karya Ading Kusdiana - Fauzan, Pepen Irpan; Fata, Ahmad Khoirul (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2019)
Pesantren as subcultures are indeed interesting to be studied. Several studies have been carried out such as Zamakhsary Dhofier on the network of pesantren in Java and Martin van Bruinessen on the pesantren and tarekat. Continuing it, Ading Kusdiana through her dissertation at Padjadjaran University conducted a research on the network of Pesantren in the Priangan region (West Java), focusing on the existence and contiÂnuity of Pesantren through five inter-Islamic networks: scientific networks, marriage, genealogical, congregational religious views, and the similarity of the vision of opposition to the invaders. Kusdiana's research confirmed Zamakhshari Dhofier's theory and did not refute it at all. So that this feels like a new work with a sense of